Efficacy of 10-valent pneumococcal non-typeable Haemophilus influenzae protein D conjugate vaccine against acute otitis media and nasopharyngeal carriage in Panamanian children – A randomized controlled trial. Issue 6 (3rd June 2017) - Sáez-Llorens, Xavier; Rowley, Stella; Wong, Digna; Rodríguez, Mirna; Calvo, Arlene; Troitiño, Marisol; Salas, Albino; Vega, Vielka; Castrejón, Maria Mercedes; Lommel, Patricia; Pascal, Thierry G.; Hausdorff, William P.; et al.
ABSTRACT: We previously reported 10-valent pneumococcal non-typeable Haemophilus influenzae (NTHi) protein D conjugate vaccine (PHiD-CV) efficacy in a double-blind randomized trial (ClinicalTrials.gov: NCT00466947) against various diseases, including acute otitis media (AOM). Here, we provide further analyses. In the Panamanian subset, 7, 359 children were randomized (1:1) to receive PHiD-CV or control vaccine at age 2/4/6 and 15–18 months. Of these, 2, 000 had nasopharyngeal swabs collected. AOM cases were captured when parents sought medical attention for children with AOM symptoms; surveillance was enhanced approximately 2 y into the study through regular telephone calls or home visits by study personnel, who advised parents to visit the clinic if their child had AOM symptoms. Mean follow-up was 31.4 months. Clinical AOM (C-AOM) cases were assessed by physicians and confirmed by otorhinolaryngologists. Middle ear fluid samples, taken from children with C-AOM after specific informed consent, and nasopharyngeal samples were cultured for pathogen identification. For 7, 359 children, 2, 574 suspected AOM cases were assessed by a primary healthcare physician; 649 cases were C-AOM cases as per protocol definition. From the 503 MEF samples collected, 158 resulted in a positive culture. In the intent-to-treat cohort (7, 214 children), PHiD-CV showed VE against first C-AOM (24.0% [95% CI: 8.7, 36.7]) and bacterial (B-AOM) episodes (48.0% [20.3, 66.1]) in children <24 months, which declined thereafter with age. Pre-booster VE against C-AOM was 30.7% [12.9, 44.9]; post-booster, −6.7% [−36.4, 16.6]. PHiD-CV VE was 17.7% [−6.1, 36.2] against moderate and 32.7% [−20.5, 62.4] against severe C-AOM. VE against vaccine-serotype pneumococcal NPC was 31.2% [5.3, 50.3] 3 months post-booster, and 25.6% [12.7, 36.7] across all visits. NTHi colonization rates were low and no significant reduction was observed. PHiD-CV showed efficacy against C-AOM and B-AOM in children younger than 24 months, and reduced vaccine-serotype NPC. Abstract :